(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, it is stated that extensive reforms were carried out in the livestock sector of agriculture in the Surkhandarya oasis. Also, in the article, the results of the reforms carried out in the field of animal husbandry in the production of meat, milk, and egg products necessary for the needs of the population, the creation of legal bases for the development of farms, and the development of the livestock sector, as well as this some measures implemented in the direction have been expressed.